Analisis Kinerja Mesin Pencuci Ubi Jalar dengan Metode Rotary Berkapasitas 25 Kg pada UMKM Grubi Manis - Cahyo Cahyo sejati; Sigit Iswahyudi; Rany Puspita Dewi (Jurnal Teknik Terapan, 2026)
Sweet potato (Ipomoea Batatas) is an agricultural commodity with high economic value that is widely used as a raw material for processed products by Micro, Small, and Medium Enterprises (MSMEs), including the sweet potato industry. In the processing process, the washing stage plays an important role in determining the level of cleanliness of the raw materials and product quality. However, at the MSME scale, sweet potato washing is generally still done manually using human power through the gejruk method, which is soaking the sweet potatoes in water accompanied by repeated mechanical force using foot treads. This method has limitations such as relatively long processing time, dependence on the operator, non-uniform levels of cleanliness, and the potential for low hygiene of the washing results. This study aims to design, build, and test the performance of a rotary-based sweet potato washing machine as an alternative to manual washing. The research methods include mechanical design, component manufacturing, and machine performance testing. The sweet potato washing machine is designed to work horizontally using a rotating tube system equipped with an internal screw, driven by a 5.5 hp gasoline motor, with a washing capacity of 25 kg in one wash, and a processing time of 7 minutes, which obtained excellent cleanliness results. The test results show that the rotary method machine is able to increase the efficiency of washing time and produce sweet potatoes that are cleaner and more hygienic than the manual method.